(untitled) (Al-Academy, 2021)
As a result of the development and global openness and the possibility of companies providing their services outside their spatial boundaries that were determined by them, and the transformation of the world due to the development of the means of communication into a large global market that accommodates all products from different regions and of the same type and production field, competition resulted between companies, and the race to obtain the largest market share It ensures the largest amount of profits, and it is natural for the advertising promotion by companies for their product to shift from an advertisement for one product to a competitive advertisement that calls on the recipient to leave the competing product and switch to its product offered by the advertised company, at the expense of the competitor who shares the revenue of profit in the same field Hence, the importance of this type of advertising has grown, as it presents a highly cultured promotional visual language that is designed in a style that has a lot of intelligence (power in offering and influence in receiving). By revealing such an important kind of promotion, the research will attempt to answer the following question: (What are the design methods used in the global competitive advertising environment?), while its objectives were set in revealing the design methods for competitive advertisements in major international commercial companies. The researcher moved to analyze selected models that showed results, most notably: the formal borrowing method achieves more absorption in the absorption of competitive advertising and thus attracts more attention. The success of the producers in the stock market. To arrive at the most prominent recommendations: Training the technical staff and informing them of the most important methods that can be implemented in the commercial markets in support of the national product in competition with the foreign product. A proposal at the end of the research a study entitled "Studying the impact of the reality of commercial competitive advertising on the national economy"